Ochlesidae - Coleman, Charles Oliver (Zootaxa, 2009)
Ochlesis alii is redescribed. It has a pointed mid-dorsal tooth on the posterior margin of pereonite 7 and a rounded process on pleonites 1 and 2. The antenna 1 has rather short pointed posterodistal processes on peduncular articles 1–2. Antenna 2 has a pointed process on peduncular article 4.